D’herbs Holding / Nur Syamimi Hazuki - Hazuki, Nur Syamimi (2021)
I had choosen the Dato Aliff Syukri company, Dherb’s Holding for my assignment. As we know, Dherb’s Holding own by Dato Aliff Syukri and his wife Datin Syahida. D’herbs holding 3 is one of the health and beauty company. They produced beauty and health product like supplements, lipstick, foundation and others. D’herbs holding is a big company. There are many challenges to build the D’herbs hoding that Dato’ Aliff faced but he determined to make sure that the company will operate smoothly. D’herbs holding started the business with only four products. Now, d’herbs holding haved around 30 beauty and health products. D’herbs Holding is now known to everyone.